The great wall of Lucy Wu - Shang, Wendy Wan Long. (New York : Scholastic, 2011)
Eleven-year-old aspiring basketball star and interior designer Lucy Wu is excited about finally having her own bedroom, until she learns that her great-aunt is coming to visit and Lucy will have to share a room with her for several months, shattering her plans for a perfect sixth-grade year.
Keywords: Individuality -- Fiction; Family life -- Fiction; Chinese Americans -- Fiction; Great-aunts -- Fiction; Schools -- Fiction